Investigation on the electron mobility and interface electric field in modulation-doped GaAs/AIGaAs heterostructures - Bailon, Michelle F. (2001)
An investigation on the dependence of electron mobility with various scattering mechanisms and measurement of the electric field at the GaAs/AlGaAs interface was carried out to characterize MBE-grown modulation-doped GaAs/AlₓGa₁ ₋ₓAs( x≈0.35) heterostructures. Hall measurement was employed to determine the resistivity, majority carrier density and the electron mobility at different temperatures (10-300K). The dependence of the mobility with various scattering mechanisms, namely iodized impurity, piezoelectric electron-acoustic phonon, phonon deformation potential and optical phonon scattering, has been determined by performing theoretical curve fitting on the experimental mobility-temperature plots from Hall measurements. The dominant scattering mechanism at specific temperature regimes was then deduced based from the curve fitting data. Results showed that at low temperature (10-50K), the piezoelectric and iodized impurity scattering were slightly dominant while phonon scattering was observed to dominate in the intermediate temperature regime (50-180K0. Optical polar scattering limits the electron mobility at high temperatures (>180K). A comparison of the mobility curves of modulation-doped heterostructure with Si-doped bulk GaAs was also performed to illustrate the difference in the behavior of the electron mobility in the two structures. at 77K, as high as 100,000 cm²/Vs mobility has been achieved in the modulation-doped heterotructure while for Si-doped bulk GaAs the mobility was only 3,000 cm²/Vs. This seemingly large difference in the mobility values was attributed to the reduced contribution of iodized impurity scattering in modulation-doped heterostructure at low temperatures. At the interface of the GaAs/AlGaAs layer, the band bending is abrupt. This causes the formation of a triangular potential well, which serves to confine most of the electronic charge (2DEG) to within 100Å of the interface. Investigation on the extent of the band bending was determined by performing measurement on the strength of the interface electric field. This was accomplished by applying FKO analysis on the photoreflectance spectrum of the modulation-doped heterostructures. The interface electric field was also estimated using result from the Hall measurements. Comparison of the obtained values revealed that the estimated value of the interface electric field based from the Hall measurement underestimates thye calculated electric field from FKO analysis by almost a factor of 2. The source of the discrepancy is yet to be verified. To determine the dependence of the interface electric field with a number of factors including doping concentration in the AlGaAs layer and the spacer layer thickness of the spacer laye